Pengaruh Burnout Terhadap Prokrastinasi Akademik Pada Mahasiswa Yang Bekerja - Sari, Ayu Kholifah; Aprianti, Melani (Merpsy Journal, 2022)
The aim of the study was to examine the effect of burnout on academic procrastination in working students. Using a descriptive quantitative design method with linear regression approach. Data collection using questionnaire google form. The sampling technique was non-probability sampling using the accidental sampling method. The research subjects obtained 203 respondents who works while studying at X University, Jakarta. The result, there is a significant effect between burnout and academic procrastination. Burnout can predict academic procrastination of 15%. Then, the burnout and academic procrastination categories are the moderate level.